Preparation, structural and dielectric properties of nanocomposite Al2O3/BaTiO3 for multilayer ceramic capacitors applications - Ahmed I. Ali; Mansour M. Hassan; G. Goda Mohammed; Hossam Youssef Abdel El-Hamid; Hilmy Awad (Journal of Materials Research and Technology, 2022)
Nano-composites ceramic of (Al2O3/BaTiO3) were successfully fabricated by Sol. Gel. technique with a weight ratio of Al2O3: BaTiO3, 1:100 wt%, respectively. X-Ray diffraction (XRD), Infrared (FT-IR), scanning electron microscopy (SEM) and Raman spectroscopy have been used to characterize the fabricated samples. Experimental data revealed that adding of Al2O3 changed both the structure and particle size of BaTiO3 from tetragonal with 7–9 μm to orthorhombic with 400–600 nm for Al2O3/BaTiO3. Moreover, SEM shows uniform grains distribution with nano-sized particles. Raman spectra shows a peak at 900 nm for BaTiO3 and split for Al2O3/BaTiO3. The FT-IR recorded several peaks related to Al2O3/BaTiO3 at low wavenumber <900 cm−1. UV/Vis spectroscopy shows an enormous peak appeared around wavelengths 550–700 nm. Finally, the dielectric properties as functions of temperature and frequency of Al2O3/BaTiO3 investigated and showed a major effect of the nanoparticles of Al2O3. Further, with increasing frequency, the complex dielectric constants of Al2O3/BaTiO3 nanocomposite decreased sharply. This can be explained by Maxwell–Wagner type of polarization in accordance with Koop's theory. The temperature dependence of complex dielectric constant exhibited phase transition of BaTiO3. The dielectric behaviors of the composites have been studied in detail to be used as the Multilayer ceramic capacitors in the electronic equipment.